The Effectiveness of Teaching an Improved Unit in Geometry According to TRIZ Theory in the Development of Creative Thinking and Cognitive Achievement - Al-Deeb, Majed (Jordan Journal of Educational Sciences, 2018)
This study aimed to identify the effectiveness of teaching an improved unit in geometry according to TRIZ theory in the development of creative thinking and cognitive achievement among eighth grade students in Gaza gover-norate. The study used the semi-experimental design. The study tools were: The teacher's guide, an achievement test and a creative thinking test in geometry. The study sample consisted of (81) female-students of the eighth grade in the Directorate of Education - East Gaza, where they were divided into two groups: The first is experimental consisting of (41) students and the other is controlling consisting of (40) students, after collecting the data and information and analyzing it statistically. The most important findings of the study were that the improved geometry unit, based on some of the principles of TRIZ theory has the greatest impact on the experimental group’s cognitive and creative thinking achievement, and that there is a positive and strong correlation between the results of the experimental group in both cognitive achievement and creative thinking